FR2.3: Participatory Rangeland Management: Understanding Women's Engagement and Implications for Social Change - Bullock, Renee; Miriti, Philip; López, Diana E. (International Livestock Research Institute, 2022)
Participatory Rangeland Management (PRM) works with customary institutions in dryland pastoral settings to strengthen communities' abilities to manage their rangelands. The process includes the creation of management committees that develop plans to manage resources that support resilience to climate change, such as restoration of grazing areas. This study describes the process of women's engagement in PRM and what it means for women's participation in decision-making processes in resource management and broader gender relations in the community and household. The study takes place in 4 communities in Baringo County, Kenya, an area severely affected by climate change effects such as drought. We use a mixed-methods approach and draw upon 56 intra-household interviews, 34 key informant interviews, and 8 FGDs. We first contextualize social change in pastoral settings, that includes describing the influence of gender sensitization efforts of development organizations and increasing numbers of women assuming leadership positions. Women actively participate in PRM committees through negotiating and advocating for protection of resources, notably those that they frequently use, such as water sources. Women also earn income from PRM related activities, that garners more support from their spouses to attend meetings. Women have also taken up so called ‘men's' activities such as beekeeping. PRM processes, that are part of wider social, economic and environmental change, bolster women's participation in decision making processes across multiple domains. Constraints however persist and limit women's potential to lead groups that include men, attend seminars, and source labor to manage domestic tasks while they participate in civic activities. These findings contribute to empirical research concerning governance of rangelands, to understanding the potential of existing frameworks to measure women's participation and provide practical lessons regarding gender responsive development.